(untitled) (Research, Society and Development, 2022)
Cagaita (Eugenia dysenterica) and Tingui (Magona pubescens) are two species of trees native to the Cerrado, with sociological, economic, and medicinal importance, besides to being used in the recovery of degraded areas. The incidence of plant diseases, as well as the mycoflora associated with their seeds, may represent a possible threat to the survival of the species. The cultivation of trees in the Cerrado Biome, as well as the diseases associated with them, are still poorly studied. The present work aimed to evaluate the mycoflora associated with Cagaita and Tingui seeds, the transmission and pathogenicity of these fungi to plants. The seeds were collected from mother trees located in the municipality of Gurupi and Figueirópolis in the state of Tocantins, Brazil. The blotter-test method was used to evaluate the mycoflora associated with the seeds of both species, with and without asepsis. The fungal incidence per seed was evaluated with the aid of a stereoscopic and optical microscope. The potentially pathogenic fungi identified in the sanitary analysis of the seeds and in the transmission, test were inoculated in the plants in order to confirm Koch’s postulates. The transmission test was carried out from non-disinfested seeds until the appearance of symptoms in the seedlings. A total of 11 fungi associated with the seeds of both species were identified. The genus Curvularia showed pathogenicity, causing spots on Cagaita leaves, being also transmitted from seeds to seedlings. The Fusarium genus showed pathogenicity in Tingui seedlings, causing damping-off and wilting. Colletotrichum sp. caused leaf spots on both species and fruit spots on Cagaita.